Epidemiological characterization of reported cases of brucellosis in cattle in the western region of the state of santa catarina, brazil - Bernardi, Fabricio; Possa, Marina Gabriela; Possa, Mariana; Nascif Junior, Iucif Abrão; Rossi, Camila Elizandra; Alves, Carlos Eduardo Fonseca [UNESP]; Elias, Fabiana (FapUNIFESP (SciELO), 2020)
Brucellosis is one of the most important and widespread bacterial zoonoses in the world. There are few epidemiological studies on brucellosis in cattle in the productive region of western Santa Catarina. Thus, the objective of this study was to characterize the epidemiological aspects of bovine brucellosis reported in this region from 2013 to 2018. Cattle data were provided by the Integrated Company for Agricultural Development of Santa Catarina (Companhia Integrada de Desenvolvimento Agrícola de Santa Catarina-CIDASC). The prevalence of the disease was evaluated in cattle and herds by means of temporal trend analysis and spatial distribution. Bovines with tests showing positive for brucellosis were analyzed for location (municipality) and year of confirmation of diagnosis. In the study period (2013-2018), 686,086 tests were performed for brucellosis, with a prevalence rate of 1.11% (7,586/686,086). Among the 80,171 herds tested, 0.95% were found to be positive (764/80171). The odds ratio of brucellosis occurrence in cattle increased significantly in 2015 (OR = 1.55) and 2016 (OR = 1.97) and decreased in 2014 (OR = 0.47) and 2017 (OR = 0.97). The disease is present in cattle in 61.07% (80/131) of the municipalities where the tests were performed. Results showed that brucellosis is endemic in the region.
Caracterização epidemiológica dos casos notificados de brucelose em bovinos na região oeste do estado de santa catarina, brasil
Keywords: Prevalence; Serology; zoonosis